Territorial public self-government as a development factor of a civil society (case of the Rakitian district of the Belgorod region) - Zhanna Mikhailovna Vodolazova; Olga Olegovna Goryanova (Вестник Майкопского государственного технологического университета, 2023)
The article considers a relevant sociological topic. The problem of the research consists in the feasibility of the development of territorial public self-government, as well as in the lack of its comprehensive scientific research as a factor in the development of civil society. The purpose of the research is to reveal the specifics and perspectives of territorial public self-government as a factor in the development of civil society. The method of “case study” has been used, a comprehensive analysis of the currently functioning territorial structures of public self-government has been carried out. The following conclusions have been formulated: the system of socially significant decision-making is multi-level and includes both small units (rural TSC) and regional governance structures; regional and municipal authorities cooperate with the structures of territorial public self-government in solving the tasks of improving the quality of life of the population, improving the natural and social environment, forming a civil society in the territory of the region. Practical recommendations have been formulated: to improve trilateral inter-sectoral cooperation aimed at the development of territorial public self-government; to actualize legal acts regulating the activities of local public structures, in part their real impact on the management decisions made by the municipal authorities, as well as the legitimate and effective implementation of citizens' initiatives; to involve representatives of different generations, as well as entrepreneurs, clergy in the TSC; to improve the system of obtaining reliable information on the opinions of citizens and social groups through the development of territorial public self-government.